Towards Effective Antiviral Oral Therapy: Development of a Novel Self-Double Emulsifying Drug Delivery System for Improved Zanamivir Intestinal Permeability - Sapir Ifrah; Arik Dahan; Nir Debotton (MDPI AG, 2023)
Self-double emulsifying drug delivery systems have the potential to enhance the intestinal permeability of drugs classified under the Biopharmaceutics Classification System (BCS) class III. One such example is the antiviral agent zanamivir, exhibiting suboptimal oral absorption (with a bioavailability range of 1-5%). To address this challenge, we have developed an innovative oral formulation for zanamivir: a self-double nanoemulsifying Winsor delivery system (SDNE-WDS) consisting of the microemulsion, which subsequently yields final double nanoemulsion (W1/O/W2) upon interaction with water. Two distinct formulations were prepared: SDNE-WDS1, classified as a W/O microemulsion, and SDNE-WDS2, discovered to be a bicontinuous microemulsion. The inner microemulsions displayed a consistent radius of gyration, with an average size of 35.1 ± 2.1 nm. Following self-emulsification, the resultant zanamivir-loaded nanoemulsion droplets for zSDNE-WDS1 and zSDNE-WDS2 measured 542.1 ± 36.1 and 174.4 ± 3.4 nm, respectively. Both types of emulsions demonstrated the ability to enhance the transport of zanamivir across a parallel artificial membrane. Additionally, in situ rat intestinal perfusion studies involving drug-loaded SDNE-WDSs revealed a significantly increased permeability of zanamivir through the small intestinal wall. Notably, both SDNE-WDS formulations exhibited effective permeability (Peff) values that were 3.5-5.5-fold higher than those of the low/high permeability boundary marker metoprolol. This research emphasizes the success of SDNE-WDSs in overcoming intestinal permeability barriers and enabling the effective oral administration of zanamivir. These findings hold promise for advancing the development of efficacious oral administration of BCS class III drugs.